Policy analysis concepts and practice - Weimer, David Leo. (Upper Saddle River Pearson Prentice Hall, 2005)
Updated in a new 5th edition, this book lays a strong conceptual foundation to understanding the rationales of and limitations to public policy. It gives practical advice about how to do policy analysis while demonstrating the application of advanced analytical techniques through case study examples.
Includes bibliographical references and index.
Keywords: Policy sciences